A novel distributed energy system combining hybrid energy storage and a multi-objective optimization method for nearly zero-energy communities and buildings. (15th January 2022) - Liu, Zhijian; Fan, Guangyao; Sun, Dekang; Wu, Di; Guo, Jiacheng; Zhang, Shicong; Yang, Xinyan; Lin, Xianping; Ai, Lei
Abstract: A distributed energy system (DES), which combines hybrid energy storage into fully utilized renewable energies, is feasible in creating a nearly zero-energy community. Improving the design, optimization, and operation of DESs is conducive to improving system performance. Therefore, a novel DES is proposed to combine a new solar energy utilization technology and hybrid energy storage ( i.e., heat storage, ice storage, and electricity storage). In addition, a new operational strategy is put forward. Subsequently, based on nearly zero-energy community and buildings, the DES configuration is optimized in relation to its environment, economy, and net interaction. Its performance and operating characteristics are compared and analysed. Then, a new indicator is proposed to evaluate the potential of the DES to achieve zero-energy. Finally, a sensitivity analysis on the carbon tax, electricity price, and equipment price is carried out. The results show that the annual carbon emissions and net interaction of the novel DES are reduced by 51.7%–73.2% and 33.5%–63.6%, respectively, compared to the reference system. Herein, the nearly zero-energy office buildings have a better zero-energy potential at 91.1%. The novel DES and corresponding multi-objective optimization method can reference a nearly zero-energy community energy supply design. Highlights: A novel distributed energy system that combines hybrid energy storage was proposed. Multi-objective optimization considering environment, economy and net interaction. Carbon emissions are declined by 73.2% in nearly zero-energy community. The nearly zero-energy office buildings have the best zero-energy potential at 91.1%. A sensitivity analysis of carbon tax and electricity price was developed.